What contributed to the major decline in per capita cigarette consumption during California's comprehensive tobacco control programme?. Issue 4 (2nd August 2006) - Gilpin, Elizabeth A; Messer, Karen; White, Martha M; Pierce, John P
Abstract : Objectives: California experienced a notable decline in per capita cigarette consumption during its comprehensive tobacco control programme. This study examines what proportion of the decline occurred from: (1) fewer ever smokers in the population, (2) more ever smokers quitting, and (3) current smokers smoking less. Design, subjects: Per capita cigarette consumption computed from cigarette sales and from adult respondents to the large, cross-sectional, population-based California Tobacco Surveys of 1990 (n = 24 296), 1996 (n = 18 616) and 2002 (n = 20 525) were examined for similar trends. Main outcome measure: Changes (period 1: 1990–1996; period 2: 1996–2002) in per capita cigarette consumption from self-reported survey data were partitioned for the entire population and for demographic subgroups into the three components mentioned above. Results: In periods 1 and 2, most of the decline in per capita cigarette consumption for the population as a whole was from current smokers smoking less followed by a reduction in ever smokers. The decline from smokers smoking less was particularly evident among young adults (18–29 years) in period 1. While the portion of the decline due to quitting in the entire population in period 1 was negligible, in period 2 it accounted for 22% of the total per capita decline. The decline from quitting in period 2 was mostly observed among women. Conclusions: Rather than near-term benefits from smokers quitting, population health benefits from reduced per capita cigarette consumption will likely occur over the longer term from fewer people becoming ever smokers, and more less-addicted smokers eventually quitting successfully.